An Efficient Transmission Power Design for SWIPT Multi-antenna Network Integrated by an Intelligent Reflecting Surface - Pham Viet Tuan; Dinh Long Hoang; Tu Ha Nguyen; Trong Duc Hoang (Tạp chí Khoa học Đại học Huế: Khoa học Tự nhiên)
In this work, intelligent reflecting surface (IRS) is integrated to improve the transmission power in the simultaneous wireless information and power transfer (SWIPT) system with hybrid time-switching (TS) users. The considered scenario includes one base station (BS), one IRS, and multiple TS users, where the BS transmits the information and energy signals to the receivers with IRS assistance. The sum transmission power minimization problem is formulated under the quality-of-service constraints of data rate and energy harvesting amount at the TS users and the equal time-switching periods. The successive convex approximation and alternating optimization methods are exploited to construct efficient algorithms for finding the suboptimal precoding beamforming vectors at the BS and the phase shifts at the IRS elements. Finally, the numerical results show convergence and significant improvement in performance as compared to conventional baseline schemes.